Liquid Crystal-Reconfigurable Antenna Concepts for Space Applications at Microwave and Millimeter Waves - A. Gaebler; A. Moessinger; F. Goelden; A. Manabe; M. Goebel; R. Follmann; D. Koether; C. Modes; A. Kipka; M. Deckelmann; T. Rabe; B. Schulz; et al. (International Journal of Antennas and Propagation)
Novel approaches of tunable devices for millimeter wave applications based on liquid crystal (LC) are presented. In the first part of the paper, a novel concept of a tunable LC phase shifter realized in Low Temperature Cofired Ceramics technology is shown while the second part of the paper deals with a tunable high-gain antenna based on an LC tunable reflectarray. The reflectarray features continuously beam scanning in between ±25∘. Also first investigations on radiation hardness of LCs are carried out, indicating that LCs might be suitable for space applications.